99.4k views
1 vote
Solve each system by using substitution.
3x - y = 4
x + 5y = -4

User Liga
by
4.9k points

1 Answer

3 votes

Answer:


from \: last \: equation : \\ x = - 4 - 5y - - - (a) \\ substitute \: in \: first \: equation \\ 3( - 4 - 5y) - y = 4 \\ - 12 - 15y - y = 4 \\ - 16y = 16 \\ y = - 1 \\ \\ therefore \: from \: (a) \\ x = - 4 - 5( - 1) \\ x = 1

User Krist
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.